Evaluation of scientific production in the field of Dentistry in Public Health from 1999 to 2009 - Luciane Zanin; Flavia Martão Florio; Roberta Blanco dos Santos; Poliana Poian Souza
Introduction: Studies that analyze scientific production are essential to guide researchers. Aim: The purpose of this study was to analyze the profile of scientific production in the field of Dentistry in Public Health, by means of the abstracts published in the Annals of Sociedade Brasileira de Pesquisa Odontológica in the period from 1999 to 2009. Material and method: First, the reading of all the 22388 abstracts published in the annals of the Sociedade Brasileira de Pesquisa Odontológica from 1999 to 2009 was undertaken. The sample was 3061 abstract belonging to Public Health area. Result: There was growing participation of studies on Dentistry in Public Health with 113 studies having been inscribed in 1999 and 441 in 2009. There was a predominance of scientific studies in comparison with systematic reviews, meta-analyses, or case reports. In the classification of general nature of the research, 71.28% concerned studies with human beings. The greatest weight in the total number of researches with humans was in 2002, contributing with 79.79% of the total. With regard to the area of thematic domain, it was verified that studies involving Epidemiology were more frequent in all the years. When analyzing the institutional origin of studies, it was verified that in all the studied years, the public universities were responsible for the majority of scientific publications, 75.6% (n=2315). Conclusion: The studies on Dentistry in Public Health have grown significantly in the studied period of ten years. There was predominance of Epidemiological studies, and those of the in vivo and scientific research type.